Retraction: Pump-assisted versus gravity-controlled enteral nutrition in long-term percutaneous endoscopic gastrostomy patients : a prospective controlled trial - Shang, Edward; Geiger, Nicole; Sturm, Jörg; Post, Stefan (Journal of parenteral and enteral nutrition, 2012)
The authors of the above article have requested its withdrawal, notifying the Journal that the clinical trials described in the article were not conducted as written in the article. The Editor-in-Chief, the American Society for Parenteral and Enteral Nutrition, and the Publisher have determined to retract the article.
Gesehen am 28.03.2022